2024
DOI: 10.1021/acssusresmgt.3c00042
|View full text |Cite
|
Sign up to set email alerts
|

Remanufacturing Perovskite Solar Cells and Modules–A Holistic Case Study

Dmitry Bogachuk,
Peter van der Windt,
Lukas Wagner
et al.

Abstract: While perovskite photovoltaic (PV) devices are on the verge of commercialization, promising methods to recycle or remanufacture fully encapsulated perovskite solar cells (PSCs) and modules are still missing. Through a detailed life-cycle assessment shown in this work, we identify that the majority of the greenhouse gas emissions can be reduced by re-using the glass substrate and parts of the PV cells. Based on these analytical findings, we develop a novel thermally assisted mechanochemical approach to remove t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…Chen et al showcased material recovery through delamination of epoxy-encapsulated devices following thermal treatment at 250 °C for 2 minutes, 43 while Bogachuk et al employed mechanically assisted thermal delamination at 120–140 °C for modules encapsulated with thermoplastic olefins (TPO) and polyisobutylene (PIB)-based edge seal. 66 These examples underscore the varying energy requirements and methodologies associated with delamination, contingent upon the sealing methods and materials used. More research is required to identify materials and methods that are not only effective for encapsulation and lead capture but also energy-efficient in application, constituted by abundant and inexpensive materials and are conducive with EoL processes.…”
Section: Recovery Of Leadmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al showcased material recovery through delamination of epoxy-encapsulated devices following thermal treatment at 250 °C for 2 minutes, 43 while Bogachuk et al employed mechanically assisted thermal delamination at 120–140 °C for modules encapsulated with thermoplastic olefins (TPO) and polyisobutylene (PIB)-based edge seal. 66 These examples underscore the varying energy requirements and methodologies associated with delamination, contingent upon the sealing methods and materials used. More research is required to identify materials and methods that are not only effective for encapsulation and lead capture but also energy-efficient in application, constituted by abundant and inexpensive materials and are conducive with EoL processes.…”
Section: Recovery Of Leadmentioning
confidence: 99%
“…In remanufacturing methods requiring the removal of layers atop the perovskite, the absence of spiro-MeOTAD presents an advantage, as the carbon layer is comparatively inexpensive. Bogachuk et al 66 recently reported a remanufacturing technique for encapsulated triple-mesoscopic carbon-PSCs with a 1.5 cm 2 active area, and assessed potential carbon footprints for 1 m 2 remanufactured modules. The proposed method involves thermally-assisted mechanical separation and acetone immersion to remove sealant and encapsulant, while methylamine and ethanol baths are used to remove the carbon layer and the degraded perovskite.…”
Section: Compatibility Of Device Design With Remanufacturingmentioning
confidence: 99%
See 1 more Smart Citation